CD24 shows early upregulation and nuclear expression but is not a prognostic marker in colorectal cancer. Issue 12 (27th November 2009) - Ahmed, M A H; Al-Attar, A; Kim, J; Watson, N F S; Scholefield, J H; Durrant, L G; Ilyas, M
Abstract : Background and aims: The putative stem cell marker CD24 is a small, heavily glycosylated, cell surface molecule which was originally associated with tumour metastasis. Recently it has been reported to be upregulated and of prognostic importance in colorectal tumours. The study aims to study the prognostic value of CD24 in a large series of colorectal cancer (CRC). Methods: CD24 protein expression was examined by immunohistochemistry. A total of 10 whole tissue sections (WTS) of adenoma and 345 CRCs arranged as tissue microarrays (TMAs) were evaluated. For comparison with non-neoplastic tissue, 10 WTS containing tumour with associated non-neoplastic tissue were also studied. Results: None of the samples of normal tissue (adjacent to tumour) showed CD24 expression. In the tumours, CD24 expression was seen on the luminal surface of the cells, within the cytoplasm and, unexpectedly, also within the nucleus. Positive immunostaining was seen in 9/10 (90%) adenomas and 313/345 (91%) of CRCs. Weak statistical associations were found between CD24 expression and some clinicopathological features. In contrast to other published studies, however, the analysis did not show any association between CD24 expression and poor prognosis—if anything it was found that loss of CD24 expression appeared to be more related to poor outcome. Conclusion: Upregulation of CD24 is an early and common event during the development of CRC and it may be expressed in any cellular compartment, including the nucleus. CD24 is not, however, a good prognostic marker in CRC.